Transvaginal Ultrasound Training for OBGYN Residents: Multi-site Randomized Controlled Trial of Educational DVD. (October 2016) - High, Brooke; McCurdy, Rebekah; Brest, Norman; Schnatz, Peter; Baxter, Jason; Jiang, Xuezhi
Abstract : BACKGROUND: Despite ongoing advances in radiologic imaging, ultrasound remains the gold standard for most gynecologic diagnoses. Current practice in OB/GYN requires its frequent use and understanding, yet formal training is typically limited. In fact, while most residencies offer organized training in obstetric ultrasound, the education in gynecologic imaging is frequently inadequate, absent or not standardized. The American Institute of Ultrasound in Medicine developed a video called "Gynecology: Beginners Only" to improve resident knowledge and skills for transvaginal ultrasound. We introduced this DVD to residents with the goal of improving competency in gynecologic ultrasound. METHODS: Residents were recruited for a multi-site prospective study using the AIUM DVD, "Gynecology: Beginners Only." All participants completed a pretest on gynecologic ultrasound images and principles. Subsequently, residents were randomly assigned to a viewing or control group. After watching the DVD, the viewers completed an identical posttest. Over a 6–10-month period, residents were encouraged to log ultrasounds on the ACGME case log system. All residents repeated the test at this time, and results were compared to prior results. RESULTS: Fifty-seven residents completed the training with a mean pretest score of 9.7 out of 15. The mean number of ultrasounds performed prior to the intervention was 31.5. The mean posttest score immediately after the intervention was improved at 11.2. However, this improvement did not persist as scores were not significantly improved several months later on a follow-up quiz for either the control or viewing groups. Hospital site, residency year, and experience did not appear to play a role in test scores. DISCUSSION: OB/GYN residents receive limited education in gynecologic ultrasound despite its frequent use. While residents would likely benefit from a structured curriculum, more research is needed to identify useful learning methods. Although the use of a DVD such as this is simple to implement and cost effective, it does not have a lasting impact on ultrasound knowledge. Exploration of different teaching modalities is necessary to create a more comprehensive training program and should likely include a hands-on component.